Factors Affecting Black Glutinous Rice Buying Decisions of Consumers in Amphoe Singhanakorn and Amphoe Khlong Hoi Khong, Songkhla Province - Phankhong, Thienchai; Chumthong, Amornrat; Saisin, Worapat (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2019)
This research aimed to 1) study the consumer requirement for Black Glutinous Rice and 2) determine the marketing strategy of Black Glutinous Rice farmers in Singhanakhon District and Khlong Hoi Khong District, Songkhla Province. The sample size comprised 400 people from the consumer groups in Amphoe Hat Yai, Amphoe Khlong Hoi Khong and Amphoe Singhanakhon, Songkhla Province. The research instrument used in this study was a structured interview recording session from a questionnaire. Data analysis used were descriptive statistics, percentages, averages, standard deviation. Inferential statistics used were Chi-square and t-test. The results showed that most consumers were older than 50 years with an income of less than 10,000 baht per month. The reason for buying Black Glutinous rice was to make food or desserts to eat with the family on an important occasions. Volume purchased averaged 1-5 kg, with buyers focusing on price, grains, color and flavor characteristics and proper packaging (41.25%) in a plastic bag like for sticky rice, while 36.25 percent wanted a plastic bag with label in full description. Significant factors that influence the decision to buy black glutinous rice include gender, age, education, family size, income, occupation and purpose in purchasing.